Correlation Analysis of Household Food Consumption Expenditure with PPH (Standard Dietary Pattern) in Sembawa District, Banyuasin Regency - Tri Yuliani, Maulidia; Mulyana, Andy; Lifianthi, Lifianthi (Journal of World Science, 2022)
Introduction: This study analyzes the correlation of food consumption expenditure on the achievement of PPH scores which is influenced by several factors such as the number of household members, non-food expenditures, and length of education. Methods: This research method is using quantitativemethods. The method of determining the number of samples used is disproportionate stratified random sampling. The data analysis method regarding the correlation of food consumption expenditure to the value of PPH uses Spearman Rank correlation analysis and the method of analyzing factors that affect household food consumption expenditure using multiple linear regression analysis methods. Result: From the results of the study, it was found that the correlation value between food consumption expenditure and the achievement of the PPH score was 0.665, which means that it is strongly correlated and simultaneously the factors that affect food consumption expenditure affect because of the significant value of f is less than 0.005 which is worth 0.00 and partially which was tested with the T-test, the results were significant only on the high-income dummy variable, which was worth 0.23 which could be interpreted that households with high incomes had higher household consumption expenditures as much as 393,336,718 compared to food consumption expenditures of medium and low-income households. Conclusion: To formulate recommendations for efforts that can be made to achieve the optimal outcome for postpartum hemorrhage, participants are expected to be able to eat well-balanced nutritious foods of good nutritional value, focusing not only on quantity but also nutritional quality and nutrition. food content.